Synthesis and therapeutic effect of styrene–maleic acid copolymer‐conjugated pirarubicin. Issue 3 (3rd February 2015) - Tsukigawa, Kenji; Liao, Long; Nakamura, Hideaki; Fang, Jun; Greish, Khaled; Otagiri, Masaki; Maeda, Hiroshi
Abstract : Previously, we prepared a pirarubicin (THP)‐encapsulated micellar drug using styrene–maleic acid copolymer (SMA) as the drug carrier, in which active THP was non‐covalently encapsulated. We have now developed covalently conjugated SMA‐THP (SMA‐THP conjugate) for further investigation toward clinical development, because covalently linked polymer–drug conjugates are known to be more stable in circulation than drug‐encapsulated micelles. The SMA‐THP conjugate also formed micelles and showed albumin binding capacity in aqueous solution, which suggested that this conjugate behaved as a macromolecule during blood circulation. Consequently, SMA‐THP conjugate showed significantly prolonged circulation time compared to free THP and high tumor‐targeting efficiency by the enhanced permeability and retention (EPR) effect. As a result, remarkable antitumor effect was achieved against two types of tumors in mice without apparent adverse effects. Significantly, metastatic lung tumor also showed the EPR effect, and this conjugate reduced metastatic tumor in the lung almost completely at 30 mg/kg once i.v. (less than one‐fifth of the maximum tolerable dose). Although SMA‐THP conjugate per se has little cytotoxicity in vitro (1/100 of free drug THP), tumor‐targeted accumulation by the EPR effect ensures sufficient drug concentrations in tumor to produce an antitumor effect, whereas toxicity to normal tissues is much less. These findings suggest the potential of SMA‐THP conjugate as a highly favorable candidate for anticancer nanomedicine with good stability and tumor‐targeting properties in vivo . Abstract : Covalently amide linked SMA‐THP conjugate showed high stability in circulation and thus prolonged circulation time and tumor targeting property based on the EPR effect. Consequently marked in vivo antitumor effects were achieved, including metastatic lung cancer, with less adverse effects, suggesting the potential of SMA‐THP conjugate as a promising candidate for cancer treatment.